(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
In this article we state the main analysis perspectives and key categories that guide the research project Urban Youth Activisms: aesthetic, migratory, racial and gender issues. It was conducted by the Brazil team together with the Red Iberoamericana de Posgrados en Infancias y Juventudes (RedINJU): an international research network constituted by the WG CLACSO (Consejo Latinoamericano de Ciencias Sociales) Infancias y Juventudes. In this first presentation, which corresponds to the initial nine months of our study, partial results are also shared regarding the reflective, contextual and conjunctural comparison of empirical data concerning some of the intersectional aspects that guide the approach with our research subjects. They’re critical, qualitative and situated readings of statistics (official and independent) on Brazilian urban youth, which concern racial and gender issues.